PENGARUH PENAMBAHAN TEPUNG MAGGOT (Hermetia illucens) PADA FORMULASI PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MAS (Cyprinus carpio) - Baiq Gustina Mardiana; Dewi Putri Lestari; Zaenal Abidin (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2023)
The purpose of this study was to determine the effect of adding maggot meal (Hermetia illucens) to feed formulations on the growth and survival of common carp (Cyprinus carpio). This research was conducted in April-May 2023 at the production and reproduction laboratory, Aquaculture Study Program, Faculty of Agriculture, University of Mataram (UNRAM). Proximate testing was carried out in the laboratory of nutrition and fedder, Faculty of Animal Husbandry, University Mataram. This study used an experimental method. The research method used Completely Randomized Design (RAL) by being tested using Analysis of Variance (ANOVA), using four treatments and three repeats P1 (0% maggot meal), P2 (10% maggot meal), P3 (20% maggot meal), P4 (30% maggot meal). The results showed that giving maggot to all treatment parameters, absolute weight, specific growth rate, feed conversion ratio (FCR), feed utilization efficiency (EPP), survival rate (SR) had a significant effect on the research tested. Conclusion The addition of different maggot meal to feed formulations can affect growth and survivalrate. The addition of maggot meal up to 30% in feed formulations in the maintenance of common carp can improve growth and survivalrate better than using feed without the addition of maggot meal.